Hysteretic behavior and simplified simulation method of high-strength steel end-plate connections under cyclic loading. (July 2019) - Sun, Fei Fei; Xue, Xuan Yi; Jin, Hua Jian; Sun, Mi; Tang, Zhi Ming; Xiao, Yong; Li, Guo Qiang
Abstract: In this study, an experiment with four high-strength steel (HSS) end-plate connections was conducted. Compared with mild steel end-plate connections, the pinching effect of HSS end-plate connections is more obvious. Based on the comparison between the experiment results and the results of EC3 formulae, the requirement in EC3 could not be directly used in the design of the HSS end-plate connection. Given that the resistance and the prying forces of the idealized HSS T-stub are usually larger than that of mild steel T-stub, the effect of the bolt bending deformation and the beam flange rotation on the connection behavior of HSS end-plate connections could not be neglected. Hence, considering the aforementioned factors, the traditional multilinear model was modified in this study. Then, based on the modified multilinear model and the experiment result, a simplified hysteresis model was introduced to simulate the hysteresis properties of HSS end-plate connections. A validation was performed to prove that the modified multilinear model and the simplified hysteresis model can be used to predict the connection behavior of the HSS end-plate connection under cyclic loading. Furthermore, similar with the HSS T-stub, there are cracks in the heat-affected zone (HAZ) of the weld between the end plate and the beam. To investigate the damage accumulation and cracking problem of the HSS end-plate connection, a weighted value β determined by the experiment results and an ultimate plastic strain of HAZ were introduced in the damage cumulative model. Highlights: A cyclic experiment is conducted to investigate hysteresis properties of high-strength steel end-plate connections. Moment-rotation curves and collapse behaviors of the HSS end-plate connection under cyclic loading are introduced. Considering the bolt bending deformation and the beam flange rotation, a modified multilinear model is proposed. A simplified hysteresis model is introduced to simulate the hysteresis properties of HSS end-plate connections. A weighted value determined by experiment results is introduced in the damage cumulative model to study cracking problem.